2004
DOI: 10.1007/s00468-004-0325-z
|View full text |Cite
|
Sign up to set email alerts
|

Biennial acorn maturation and its relationship with flowering phenology in Iberian populations of Quercus suber

Abstract: Since the XIX century, there is a controversy about the existence of biennial maturation of the acorns in Quercus suber L. While some authors recognised biennial cycles as an adaptation to habitats with short vegetative periods, other authors discarded the biennial pattern. Successive flowering events from spring to autumn and annual acorn ripening are proposed as an explanation of the multiple acorn crops typical of Iberian forests. To clarify this discussion, the presence of annual and biennial acorns was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 24 publications
(24 reference statements)
1
24
1
Order By: Relevance
“…Gómez (2004) fits acorn weight to a log-normal distribution, with mean varying in two years from 2.25 ± 0.02 g to 2.64 ± 0.03 g, also under a continental Mediterranean climate, however 200 mm more humid in average than Afzal-Raffii et al's continental site. The reduction of acorn size as a response of the shorter, cooler growing season has been reported elsewhere for other oak species (Aizen and Woodcock, 1992;Díaz-Fernández et al, 2004).…”
Section: Acorn Size and Morphologysupporting
confidence: 71%
See 3 more Smart Citations
“…Gómez (2004) fits acorn weight to a log-normal distribution, with mean varying in two years from 2.25 ± 0.02 g to 2.64 ± 0.03 g, also under a continental Mediterranean climate, however 200 mm more humid in average than Afzal-Raffii et al's continental site. The reduction of acorn size as a response of the shorter, cooler growing season has been reported elsewhere for other oak species (Aizen and Woodcock, 1992;Díaz-Fernández et al, 2004).…”
Section: Acorn Size and Morphologysupporting
confidence: 71%
“…Some authors have suggested the hypothesis that woody species with longer intermast interval are likely to produce larger seeds, likely as an adaptation to increase seedling survival (Aizen and Woodcock, 1992;García et al, 2000;Sork, 1993). It has been shown in some oak species how acorn size correlates positively with the length of its development period and with rainfall (Sork, 1993;Díaz-Fernández et al, 2004).…”
Section: Acorn Size and Morphologymentioning
confidence: 99%
See 2 more Smart Citations
“…Since cork oak bears both annual and biennial fruiting (Corti, 1955;Díaz-Ferná ndez et al, 2004), the latter was excluded simply by starting the observations simultaneously with holm oak fruiting.…”
Section: Methodsmentioning
confidence: 99%